2001
DOI: 10.1097/00002030-200103090-00005
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-related pleural tuberculosis: elevated production of IFN-γ, but failure of immunity to Mycobacterium tuberculosis

Abstract: HIV-positive patients with pleural tuberculosis show elevated production of IFN-gamma, for which CD8+ T cells may be a major source. Mycobacterium tuberculosis can proliferate despite high levels of pro-inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Many investigators have evaluated cytokine levels either in plasma or in culture supernatants of PBMCs obtained from patients with HIV or TB, (10)(11)(12) but only a few have measured IFN-g levels in patients with dual infection. (13,14) We found that in TB patients with HIV infection, in vitro IFN-g production in response to mycobacterial antigens was variable but tended to be lower than in TB patients without HIV infection. Elliott et al (14) also reported profoundly impaired IFN-g responses to mycobacterial antigens in HIV patients with TB.…”
Section: Discussionmentioning
confidence: 93%
“…Many investigators have evaluated cytokine levels either in plasma or in culture supernatants of PBMCs obtained from patients with HIV or TB, (10)(11)(12) but only a few have measured IFN-g levels in patients with dual infection. (13,14) We found that in TB patients with HIV infection, in vitro IFN-g production in response to mycobacterial antigens was variable but tended to be lower than in TB patients without HIV infection. Elliott et al (14) also reported profoundly impaired IFN-g responses to mycobacterial antigens in HIV patients with TB.…”
Section: Discussionmentioning
confidence: 93%
“…Crude culture filtrate proteins (CFPs) of M. tuberculosis H37Rv were provided by J. T. Belisle (Colorado State University, Fort Collins), courtesy of the National Institutes of Health (National Institute of Allergy and Infectious Diseases grant NO1 AI-75320). This antigen is composed primarily of antigen 85, a secreted protein complex that is involved in the synthesis of the cell wall and is immunogenic in humans [20][21][22][23]. S. mansoni adult worm antigen (SWA) and S. mansoni egg antigen (SEA) were prepared as described elsewhere [24].…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Although the authors acknowledged that this may not have equated to increased levels of the cytokine, the presence of this marker on the cells is an important difference which may explain the progression of pleural TB in HIV-infected patients in HIV-infected patients since apoptotic activity has been linked with TNF α and its continued presence is detrimental to the cellular environment [44] resulting in caseating necrosis. In another study, TNF α was elevated in HIV-pleural TB compared to HIV-uninfected pleural TB but the difference was not statistically significant [14]. In this same study, IFN γ was significantly elevated in serum and pleural fluid in HIV-pleural TB compared to HIV-uninfected pleural TB and it was suggested that CD8+ T cells could be the source which is supported by another study showing a relative increase in CD8+ T cells in HIV-positive patients with pleural TB [14].…”
Section: Immunopathogenesis Of Pleural Tb In Hivinfected Patientsmentioning
confidence: 99%
“…In another study, TNF α was elevated in HIV-pleural TB compared to HIV-uninfected pleural TB but the difference was not statistically significant [14]. In this same study, IFN γ was significantly elevated in serum and pleural fluid in HIV-pleural TB compared to HIV-uninfected pleural TB and it was suggested that CD8+ T cells could be the source which is supported by another study showing a relative increase in CD8+ T cells in HIV-positive patients with pleural TB [14]. However, mycobacterial replication was not controlled in the pleural space despite high levels of IFN γ .…”
Section: Immunopathogenesis Of Pleural Tb In Hivinfected Patientsmentioning
confidence: 99%